Programa de Controle de Cães e Gatos do Estado de São Paulo - Módulo VII - Legislação e políticas públicas - Lopes Vieira, Adriana Maria; Batista de Almeida, Aparecido; Magnabosco, Cristina; Pinheiro Ferreira, João Carlos; Loureiro Pacca Luna, Stélio; Brant de Carvalho, Lotufo; Hardt Gomes, Luciana; Tucunduva Paranhos, Noemia; Reichmann, Maria de Lourdes; Garcia, Rita de Cassia; Plaza Nunes, Vania de Fátima; Benini Cabral, Viviane (BEPA. Boletim Epidemiológico Paulista, 2006)